PEMBINAAN PERAN GEREJA DALAM MEMBANGUN KESADARAN KEWARGANEGARAAN DI ERA DIGITAL BAGI MASYARAKAT RULI PUTRI 7 MANDIRI RT.04 RW.06 KELURAHAN KIBING KECAMATAN BATU AJI BATAM - Purba, Gomgom; Sidabutar, Triades Sidabutar; Setya Budi (JURNAL BEATITUDES, 2024)
Abstract The purpose of this community service is to socialize and implement the development of the church's role in building citizenship awareness in the digital era for the Ruli Putri 7 Mandiri Rt.04 Rw.06 community of Kibing Village, Batu Aji District. This community service uses a qualitative approach methodology with descriptive analysis. Data were collected through literature studies from various sources, including books, journal articles, and relevant community service reports. In addition, interviews with church leaders and congregation members were also conducted to obtain a direct perspective on the role of the church in citizenship. This study also involves case analysis of churches that have succeeded in building citizenship awareness in their communities. The interviews were conducted with and the community at the PkM location. The results of the development of the church's role in building citizenship awareness in the digital era for the Ruli Putri 7 Mandiri Rt.04 Rw.06 community of Kibing Village, Batu Aji District, namely the Development of the Church's Role in Citizenship through a community empowerment program initiated by the church also shows the church's commitment to improving the quality of life of the congregation and the surrounding community. The Church's Use of Digital Media for Civic Education allows the church to be more responsive to current issues affecting society. Finally, it is important to realize that civic education is an ongoing process. The church needs to continue to adapt to changing times and technological developments to remain relevant in educating its members to maximize their role. Keywords: Formation, citizenship, digital era